2005
DOI: 10.1002/pam.20160
|View full text |Cite
|
Sign up to set email alerts
|

The effectiveness of regulatory disclosure policies

Abstract: Regulatory transparency-mandatory disclosure of information by private or public institutions with a regulatory intent-has become an important frontier of government innovation. This paper assesses the effectiveness of such transparency systems by examining the design and impact of financial disclosure, nutritional labeling, workplace hazard communication, and five other diverse systems in the United States. We argue that transparency policies are effective only when the information they produce becomes “embed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
169
0
5

Year Published

2008
2008
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 210 publications
(180 citation statements)
references
References 77 publications
5
169
0
5
Order By: Relevance
“…As Weil et al (2006) have shown in the context of information policies, whether and how information is used depends on its incorporation into complex chains of comprehension, action, and response. For example, the presence of competing eco-labels might lead to consumer confusion (Leire & Thidell, 2005).…”
Section: The Pitfalls Of Eco-labelingmentioning
confidence: 99%
“…As Weil et al (2006) have shown in the context of information policies, whether and how information is used depends on its incorporation into complex chains of comprehension, action, and response. For example, the presence of competing eco-labels might lead to consumer confusion (Leire & Thidell, 2005).…”
Section: The Pitfalls Of Eco-labelingmentioning
confidence: 99%
“…As a result, policymakers frequently pair choice mechanisms with transparency systems-such as public school report cards, nutritional labeling, toxic pollution reporting, auto safety and fuel economy ratings, and corporate financial reporting (Weil et al 2006)-all intended to make comparative information readily available.…”
Section: Introductionmentioning
confidence: 99%
“…This imperative of accountability encourages transparency in the decisional and administrative processes since citizens are no longer satisfied simply with the results, but are increasingly interested in the process. Literature on democracy (Chambers 2004) and risk policies (Weil et al 2006) has devoted efforts to develop a link between transparency and efficacy.…”
Section: Introductionmentioning
confidence: 99%